Analisis Dampak Media Sosial Terhadap Perkembangan Bahasa Gaul Pada Remaja Di Tambun Utara - Rizki, Muhammad Rizki Fauzi; Samosir, Astuti; Haryati , Ade Siti (Jurnal Pendidikan Impola, 2026)
In today's digital era, social media has become an inseparable part of everyday life, especially among teenagers. The rapid development of information and communication technology has influenced social interaction patterns, including communication methods and language use. This study aims to examine in depth how social media impacts the development and spread of slang among teenagers living in North Tambun. This study uses a qualitative descriptive approach with a case study method. Data collection was conducted through observations of teenagers' activities on social media, in-depth interviews with several informants, and documentation of digital conversations on platforms such as Instagram, TikTok, and WhatsApp. The results show that social media is not only a means of communication but also functions as a creative space for creating, modifying, and disseminating new forms of slang. The new vocabulary that emerges is often brief, symbolic, and adaptive to the context of popular cultural trends. Teenagers quickly absorb and adopt these new terms as part of their social identity. This phenomenon contributes to the richness of language in informal contexts, but also raises concerns about the decline in teenagers' ability to use standard and appropriate Indonesian.Keywords: social media, Language gaul, teenagers, North Tambun